PRINCIPLES OF LENINIST PARTISANSHIP IN LITERATURE AND ART - Choriyev Sanjar Hamzaevich (Journal of Learning on History and Social Sciences, 2024)
The partisanship of Soviet literature and art, the Marxist-Leninist doctrine and party leadership of literature and art, and the manifestation of partisanship in Uzbek Soviet literature and art are discussed